Innovations and technologies in construction : special topic volume with invited peer-reviewed papers only - Klyuev, Sergey Vasil'yevich (Materials science forum ;, 2021)
The important problems of Building Constructions, Building Materials, Industrial and Civil Construction, and Structural Mechanics and Theory of Structures (from ideas and projects to immediate implementation) are raised, and the ways of their solution and optimization are suggested in the reports presented in frameworks of these topics. Many reports were prepared as a benefit of the state support of science in the forms of grants, federal target programs, resolutions of the Government of the Russian Federation, and other programs.